Essential role of the electroneutral Na+–HCO3− cotransporter NBCn1 in murine duodenal acid–base balance and colonic mucus layer build‐up in vivo. (11th March 2013) - Singh, Anurag Kumar; Xia, Weiliang; Riederer, Brigitte; Juric, Marina; Li, Junhua; Zheng, Wen; Cinar, Ayhan; Xiao, Fang; Bachmann, Oliver; Song, Penghong; Praetorius, Jeppe; Aalkjaer, Christian; et al.
Key points: In the upper intestinal tract, luminal acidity due to intermittent release of gastric juice needs to be counteracted by basolateral HCO3 − import. In the lower gastrointestinal tract, the build‐up of a thick mucus layer is a major defence mechanism against pathogens, and HCO3 − is of the utmost importance for this process. The pathways for HCO3 − transport that play a role in these mucosal defence strategies are, however, unknown. We recently identified the electroneutral Na + –HCO3 − cotransporter NBCn1 as a major regulator of intracellular pH in duodenal villous enterocytes. The present study shows that the murine duodenocytes, whose intracellular pH was monitored by in vivo two‐photon confocal microscopy in anaesthetized NBCn1 knock‐out mice, are unable to recover rapidly from intracellular acidification imposed by a short pulse of low‐pH solution in the duodenal lumen. Likewise, they are not able to respond to contact of the surface with low pH by a protective HCO3 − secretory response. The cotransporter NBCn1 is also expressed in the basolateral membrane of colonic crypt cells, many of which stain positive for mucin granules. We found only a minor role for NBCn1 in colonic epithelial HCO3 − secretion, but the build‐up of a mucus layer, measured in the exteriorized colon of anaesthetized mice by in vivo microscopy, was significantly delayed in the absence of NBCn1 expression. Therefore, NBCn1 plays major but different roles in mucosal protective functions in the upper and lower intestine. Abstract Duodenal epithelial cells need efficient defence strategies during gastric acidification of the lumen, while colonic mucosa counteracts damage by pathogens by building up a bacteria‐free adherent mucus layer. Transport of HCO3 − is considered crucial for duodenal defence against acid as well as for mucus release and expansion, but the transport pathways involved are incompletely understood. This study investigated the significance of the electroneutral Na + –HCO3 − cotransporter NBCn1 for duodenal defence against acid and colonic mucus release. NBCn1 was localized to the basolateral membrane of duodenal villous enterocytes and of colonic crypt cells, with predominant expression in goblet cells. Duodenal villous enterocyte intracellular pH was studied before and during a luminal acid load by two‐photon microscopy in exteriorized, vascularly perfused, indicator (SNARF‐1 AM)‐loaded duodenum of isoflurane‐anaesthetized, systemic acid–base‐controlled mice. Acid‐induced HCO3 − secretion was measured in vivo by single‐pass perfusion and pH‐stat titration. After a luminal acid load, NBCn1‐deficient duodenocytes were unable to recover rapidly from intracellular acidification and could not respond adequately with protective HCO3 − secretion. In the colon, build‐up of the mucus layer was delayed, and a decreased thickness of the adherent mucus layer was observed, suggesting that basolateral HCO3 − uptake is essential for optimal release of mucus. The electroneutral Na + –HCO3 − cotransporter NBCn1 displays a differential cellular distribution in the murine intestine and is essential for HCO3 − ‐dependent mucosal protective functions, such as recovery of intracellular pH and HCO3 − secretion in the duodenum and secretion of mucus in the colon.